Assessment the awareness of vitamin D deficiency among the general population in Syria: an online cross-sectional study - Hidar Alibrahim; Sarya Swed; Haidara Bohsas; Yasmeen Abouainain; Nagham Jawish; Rehab Diab; Angela Ishak; Heba Haj Saleh; Mohamad Nour Nasif; Rahaf Arafah; Wajih Abboud Abboud; Asma'a Horan Suliman; et al. (BMC, 2024)
Abstract Background Vitamin D deficiency is an importance preventable problem in the global and associates with lack levels of awareness about vitamin D. According to prior studies, in the Arab world, there is low of knowledge and awareness toward vitamin D deficiency. The target of our study is evaluating the knowledge level about vitamin D deficiency and determining the associated factors with levels of awareness of its. Method This online cross-sectional study was performed in Syria between 25 February to 29 March 2023 to assess the levels of knowledge about vitamin D deficiency among general Syrian population. The study's survey was obtained from previously published research and we conducted a pilot study to assure the validity and clarity questionnaire. All Syrian individuals aged 18 or older who were able to read and write and willing to participate were included, while, non-Syrian nationality individuals and all medical staff (doctors, nurses, and medical students...), as well, those under 18 age were excluded. The questionnaire consisted of 23 questions separated into four categories. The first section was sociodemographic information of the study population. The second section measured the level awareness of the study population regarding the benefits of vitamin D. In addition, the third and fourth part evaluated knowing of the respondents about sources of and toxicity consequences of vitamin D. The data were analyzed by utilizing multivariate logistic regression in IBM, SPSS V.28 version. Results Overall, 3172 of the study population accepted to participate in this research and 57.9% the majority of them were aged in the range among 18 and 28. While, the average age of the respondents were 30.80 ± 11.957. Regarding with the awareness toward knowledge of advantages and source of vitamin D and outcomes of vitamin D toxicity. Most of the participants mentioned that vitamin D is used to treat bone disease and rickets and contributes in maintaining calcium and phosphates (91.4% and 84.6%, respectively). Whereas, more than half of them reported that sun exposure does not cause vitamin D poisoning and that vegetarians are more likelihood to have vitamin D than non-vegetarians, (54.1% and 54.9%, respectively). Only, age and occupation out of nine predictors variables were significantly correlated with adequate knowledge of Vitamin D (p-value < 0.05). The respondents aged more than 60 years were high probability to have good recognition of Vitamin D than participants aged between 18 and 28 years. (OR = 7.95). Retired participants have shown lower aware of Vitamin D 0.38 times than students. Conclusion Our research revealed that most of the participated individuals have sufficient comprehension about vitamin D, despite, there were significant gap. Health education via programs by government health-care agencies, NGOs and social workers is necessary to increase the awareness and knowledge toward benefits, source, deficiency and toxicity of vitamin D to avoid injury several diseases such as rickets.